Природодослідники Харківського ветеринарного інституту (ХІХ століття) - Цюняк, О. В. (НТУ "ХПІ", 2011)
У даній статті розглядаються основні принципи єднання викладацької і науково-дослідної роботи вчених Харківського ветеринарного інституту наприкінці ХІХ століття. Хронологічно розкрито наукові напрями розвитку ветеринарної медицини, які були тісно пов’язані з економічним життям країни

The main principles of teaching and scientific research work unification of Kharkiv Veterinary Institute at the end of the XIX century are considered. Scientific trends of veterinary medicine development which closely connected with economical conditions of the country are analyzed chronologically
Keywords: ветеринарна медицина; наукові напрями; вчені; тваринництво; scientific research work; scientific trends; veterinary medicine; economical conditions